HARNESSING AUGMENTED REALITY FOR INTERACTIVE LEARNING IN ISLAMIC EDUCATION - Tajdidul Islahi, Bilad; Hakim, Rahmad (International Journal of Multidisciplinary Reseach, 2025)
Education plays a strategic role in shaping civilization and maximizing human potential. Yet conventional teaching approaches often struggle to effectively raise students’ motivation and understanding, particularly within Islamic Religious Education (IRE). Technological advances offer viable alternatives through interactive media such as Augmented Reality (AR), which enables concrete visualization of learning content. This study seeks to examine the use of AR as an interactive learning medium in IRE using a literature review approach. Research articles were identified via Google Scholar with the keywords “Augmented Reality,” “Interactive Learning Media,” and “Islamic Religious Education,” and were screened for relevance, publication within the last five years (2021–2025), and accessibility. The review indicates that AR substantially improves student motivation, comprehension, and engagement, especially for topics such as the history of Muslim scientists, funeral rites, sīrah nabawiyyah, tajwīd, and the practice of Hajj and ‘Umrah. By addressing the limitations of traditional methods, AR emerges as a meaningful innovation in contemporary education and is expected to support more relevant and transformative learning experiences. These findings also highlight implications for curriculum design, teacher training, and assessment.